2021
DOI: 10.3389/fonc.2021.687432
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Skin Cancer in Patients With Chronic Inflammatory Cutaneous Diseases on Targeted Therapies: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Cancer is one of the several comorbidities that have been linked with chronic cutaneous inflammatory diseases namely psoriasis/psoriatic arthritis and hidradenitis suppurativa. Although the chronic inflammatory state, typical of the diseases, may induce pro-tumorigenic effects, the debate whether or not the drugs currently used in clinical practice do in facts increase a patient’s risk of malignancy remains largely unsolved. The therapeutic armamentarium has been greatly enhanced at least in the last two decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…In accordance with these findings, a recent systematic review and meta-analysis suggests no differences exist for induction of melanoma between treatment of chronic cutaneous diseases with TNFi or ustekinumab and treatment with conventional systemic immunosuppressive drugs, while data on NMSC are more controversial. These results are in agreement with those obtained from the German Psoriasis Registry PsoBest, performed in 2008, with a follow-up period of 10 years; in this cohort, no relevant differences were found among any of these drugs with respect to melanoma skin cancer and non-melanoma skin cancer [ 47 , 48 ].…”
Section: Psoriasis Therapies and Skin Cancersupporting
confidence: 90%
“…In accordance with these findings, a recent systematic review and meta-analysis suggests no differences exist for induction of melanoma between treatment of chronic cutaneous diseases with TNFi or ustekinumab and treatment with conventional systemic immunosuppressive drugs, while data on NMSC are more controversial. These results are in agreement with those obtained from the German Psoriasis Registry PsoBest, performed in 2008, with a follow-up period of 10 years; in this cohort, no relevant differences were found among any of these drugs with respect to melanoma skin cancer and non-melanoma skin cancer [ 47 , 48 ].…”
Section: Psoriasis Therapies and Skin Cancersupporting
confidence: 90%
“…The possible role that the TNF-alpha inhibitor played in the development of SCC on HS lesions, and concomitant sepsis, was unclear, because there was just a significant baseline immune dysregulation in their patient and an increased infectious risk were clearly reported with this drug class [ 6 ]. How and to what extent TNF-alpha inhibitors may promote the development of NMSC still remains controversial [ 10 ]. Sure enough, a meta-analysis of 74 randomized controlled trials failed to confirm or refute that anti-TNF-alpha agents caused an increase in the development of malignancy [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also an association with autoimmune comorbidities with a significant overlap between patients with HS and inflammatory bowel disease (IBD), especially Crohn’s disease (CD) [ 6 , 8 ]. Several case reports of co-occurrence of HS and nonmelanoma skin cancer suggested a causal relationship, but firm epidemiological data are lacking [ 9 , 10 ]. In an attempt to assess the link between HS and cancer, we performed a systematic review of the current literature on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…89 In the past two decades, increasing evidence of the association between NMSC and HS has emerged. [90][91][92][93][94] The prevalence of NMSC amongst these patients is estimated to be between 0.5% to 4.6%. 95,96 A study of over 2000 Swedish patients with HS showed that these patients have a 4.6-fold increased risk for developing NMSC.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%